2022
DOI: 10.1051/e3sconf/202233500013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary inclusion of black soldier fly larvae (Hermetia illucens) on broiler performance: A meta-analysis

Abstract: Black Soldier Fly (BSF, Hermetia illucens) is an insect species that potentially can be used as a protein source for broiler nutrition. This study aimed to evaluate different inclusion level of BSF on broiler performance and blood metabolites by integrating various data from related studies using meta-analysis. Total of 12 studies that comprised of 31 data points were integrated in the database. Parameters observed included Live Weight (LW), Average Daily Gain (ADG), Daily Feed Intake (DFI), Feed Conversion Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In general, in this study BSFL dietary inclusion had no effect on the carcass and cut-up percentage. Several studies conducted in broiler chicken found that supplementing with BSF meal had no effect on the carcass percentage of broilers [16].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In general, in this study BSFL dietary inclusion had no effect on the carcass and cut-up percentage. Several studies conducted in broiler chicken found that supplementing with BSF meal had no effect on the carcass percentage of broilers [16].…”
Section: Resultsmentioning
confidence: 98%
“…Total meat protein from groups T1 and T2 is similar to T0 groups, although BSFL is known as a high protein source feedstuff, but BSFL meal has a lot of chitin, which is indigestible and can reduce protein digestibility. The chitin in the exoskeleton of HI larval Chitin was shown to have a detrimental impact on protein digestion [16].…”
Section: Resultsmentioning
confidence: 99%
“…Chodová and Tůmová (2020) reviewed a number of studies, and found that insect meals can have a positive influence on growth of chickens without negative impact on carcass and meat quality characteristics. Nayohan et al (2022) reviewed 12 studies concluding that feeding of broilers with black soldier fly negatively affect their performance. This is probably the reason that optimal inclusion levels need to be established for products from different insect species and per poultry species (Dörper et al 2021).…”
Section: Chickensmentioning
confidence: 99%
“…Nayohan et al . (2022) reviewed 12 studies concluding that feeding of broilers with black soldier fly negatively affect their performance. This is probably the reason that optimal inclusion levels need to be established for products from different insect species and per poultry species (Dörper et al .…”
Section: Insects Used For Feedmentioning
confidence: 99%